Numerical Study of Characteristics Root Canal Irrigation using Open-Ended Needle Positive Pressure and Negative Pressure Method - Fajar Dwi Yudanto; Wawan Aries Widodo; Suwarno Suwarno (JMES: The International Journal of Mechanical Engineering and Sciences, 2020)
This study aims to determine the characteristics of fluid flow through root canal irrigation using positive and negative pressure methods used CFD (Computational Fluid Dynamic) software by modeling root canals and needle insertion in the root canals. This modeling used a steady flow, an incompressible flow, and uniform flow at the inlet side, and the roughness of the root canal wall surface is neglected (smooth wall). The open-ended needle with different insertion lengths applied for each method with a flow rate of 0.2 mL/s or about 6.63 m/s and the Reynolds number is 1376 (Laminar). The fluid has 2.5% of NaOCl with the density of 1060 kg/m3 and 0.001 Pa.s of fluid viscosity. After considering factors such as velocity, dynamic pressure, and wall shear stress in both methods, a greater velocity value in the apical region is determined by using a positive pressure method. Meanwhile, the negative pressure method shows the ability to lift higher due to shear stress, which is more evenly distributed upwards. However, both methods are qualified for irrigation replacement in the apical region.